Metformin Inhibits Lipoteichoic Acid–Induced Oxidative Stress and Inflammation Through AMPK/NRF2/NF-κB Signaling Pathway in Bovine Mammary Epithelial Cells - Arbab, Abdelaziz Adam Idriss; Lu, Xubin; Abdalla, Ismail Mohamed; Idris, Amer Adam; Chen, Zhi; Li, Mingxun; Mao, Yongjiang; Xu, Tianle; Yang, Zhangping (Frontiers in Veterinary Science, 2021)
This research’s objective was to explore the effect of metformin on the Lipoteichoic acid (LTA)-induced mastitis model using isolated primary bovine mammary epithelial cells (PBMECs). The PBMECs were exposed either to 3 mM metformin for 12 h as a metformin group (MET), or 100 μg/mL LTA for 6 h as LTA group (LTA). Cells pretreated with 3 mM metformin for 12 h followed by washing and 100 μg/mL LTA exposure for 6 h were served as (MET+LTA) group. PBS was added to cells as the control group. PBMECs pretreated with different metformin doses were analyzed by a ﬂow cytometry (Annexin V-FITC assay) to detect the cell apoptotic rate. We performed qRT-PCR and western blot analysis to evaluate the inﬂammatory and oxidative responses to metformin and LTA by measuring cellular cytotoxicity, mRNA expression, and protein expression. Immunoﬂuorescence was used to evaluate nuclear localization. The results showed that the gene expression of COX2, IL-1β, and IL-6 significantly increased in the cells challenged with LTA doses compared to control cells. In inflammatory PBMECs, Metformin attenuated LTA-induced expression of inflammatory genes NF-κB p65, TNFα, COX2, and IL-1β, as well as the nuclear localization and phosphorylation of NF-κBp65 protein; however, increased the transcription of Nrf2 and Nrf2-targeted antioxidative genes HO-1 and Gpx1, also the nuclear localization of HO-1 protein. Importantly, metformin-induced activation of Nrf2 is AMPK-dependent; as metformin pretreated PBMECs activated AMPK signaling via the upregulation of phosphorylated AMPK levels, cells pretreatment with metformin also reversed the translocation of Nrf2 that was LTA inhibited. This convergence between AMPK and Nrf2 pathways is essential for the anti-inflammatory effect of Metformin in LTA-stimulated PBMECs. Altogether, our results indicate that metformin exerts anti-inflammation and oxidative stress through regulation of AMPK/Nrf2/NF-κB signaling pathway, which highlights the role of AMPK as a potential therapeutic strategy for treatment of bovine mastitis.